Monoatom doped M-B-C material, and preparation method and application thereof
By annealing the mixture of metal boride and graphene under an argon-hydrogen atmosphere, a single-atom doped M-B-C material with multi-layer nanosheet structure was prepared, which solved the problem of metal atom agglomeration and achieved efficient electrochemical performance improvement. It is suitable for the negative electrodes of lithium, sodium and potassium ion batteries.
Patent Information
- Application Number
- CN202510514380.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-07-11
AI Technical Summary
In the prior art, when preparing single-atom doped M-B-C materials, high-temperature annealing treatment can easily lead to agglomeration of metal atoms, affecting the formation efficiency of single-atom structures, and making it difficult to achieve precise regulation and controllable preparation.
The single-atom doped M-B-C material with multi-layer nanosheet structure was prepared by stirring metal boride and graphene in water, and then annealing treatment under an argon-hydrogen atmosphere to control the annealing temperature and temperature increase rate.
It achieves a high degree of dispersion and stable existence of metal atoms, improves the specific surface area and active sites of the material, and shows excellent electrochemical properties. It is suitable for lithium, sodium, and potassium ion battery negative electrode materials.
Smart Images

Figure CN120300183A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy storage battery materials, and particularly relates to a single-atom doped M-B-C material, a preparation method thereof, and an application thereof. Background Art
[0002] With the increasing depletion of traditional fossil energy such as petroleum and coal and the increasingly severe environmental problems caused by them, the traditional energy system dominated by fossil energy is facing an unprecedented survival crisis and development challenge. In this context, accelerating the research and development process of new renewable clean energy has become an urgent task for global energy transformation. Currently, the mainstream clean energies mainly include wind energy, water energy, solar energy, and new-generation energy storage battery technology. In the field of energy storage batteries, alkali metal ion batteries (lithium, sodium, potassium systems) have become a research hotspot. Among them, lithium-ion batteries have been widely used in new energy vehicles, consumer electronics, medical equipment and other fields due to their excellent open-circuit voltage, high energy density, and good environmental compatibility. However, sodium and potassium ion batteries have a broader commercial application prospect because of their rich resource reserves, wide geographical distribution, low manufacturing cost, excellent rate performance and cycle stability.
[0003] In the forefront of alkali metal battery research, single-atom materials are attracting great attention in the academic community due to their nearly 100% atomic utilization rate, significant cost advantages, unique strong metal-support interaction, and adjustable coordination environment characteristics. In particular, the anode material composed of atomically dispersed transition metals anchored on a boron-doped carbon matrix (M-B-C) exhibits extraordinary electrochemical performance. Researchers first successfully prepared a single-atom doped M-B-C material by high-temperature annealing reduction method. As the anode of alkali metal ion batteries, this material has indeed achieved performance improvement. However, the current process mainly relies on annealing temperature control to change the coordination environment of metal atoms. This high-temperature treatment is extremely likely to cause metal atom agglomeration, seriously restricting the formation efficiency of single-atom structures. Therefore, how to break through the existing technical bottleneck and achieve precise control and controllable preparation of single-atom metal sites has become the key scientific problem for promoting the practical application of M-B-C nanomaterials, and its research value and industrial significance are self-evident. Summary of the Invention
[0004] The purpose of the present invention is to develop a new anode material with stable structure, moderate working voltage, and capable of meeting the rapid shuttling of ions, and to provide a single-atom doped M-B-C material, a preparation method thereof, and an application thereof. It has a multi-layer nanosheet structure, with metal atoms highly dispersed, a relatively high specific surface area, and rich active sites; and the involved preparation method is relatively simple, and it is applied to the field of alkali metal ion batteries (lithium, sodium, potassium).
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: A preparation method of single-atom doped M-B-C material, comprising the following steps: 1) Disperse metal boride in water, add hydrogen peroxide and stir until the metal boride is dissolved. After standing for at least 20 h, add graphene and stir at room temperature until a uniform solution is obtained, and then freeze-dry; 2) Anneal the dried product obtained in step 1) in an argon / hydrogen mixed atmosphere, and cool to room temperature to obtain the product.
[0006] Further, the metal boride in step 1) is titanium boride, molybdenum boride, niobium diboride, cobalt boride, vanadium boride, tungsten boride, iron boride, zirconium diboride, chromium diboride, magnesium diboride or aluminum diboride.
[0007] Further, in step 1), the ratio of the metal boride to hydrogen peroxide is (0.2~0.5) g:(10~30) mL.
[0008] Further, the mass ratio of the graphene to the metal boride is (1~3):1, and the number of layers of the graphene ≤ 5 layers.
[0009] Further, the temperature of the freeze-drying is -30~-50 °C, and the time of the freeze-drying is 24 h~72 h.
[0010] Further, in the argon / hydrogen mixed atmosphere in step 2), the volume ratio of argon to hydrogen is (8~10):1, and the hydrogen partial pressure is controlled at 0.1~0.3 MPa.
[0011] Further, the annealing temperature in step 2) is 300~350 °C; the heating rate used is 2~5 °C / min, and the holding time is 3~5 h.
[0012] The single-atom doped M-B-C material prepared by the above preparation method.
[0013] The application of the above single-atom doped M-B-C material in lithium, sodium or potassium ion batteries.
[0014] Further, the single-atom doped M-B-C material is used as an active substance and coated on a current collector as a negative electrode.
[0015] Mix the atom-doped M-B-C material, conductive agent, and binder evenly according to (6~8):(1~3):1, add an appropriate amount of NMP or water, and grind until there are no obvious particles in the slurry. Then coat it evenly on the copper foil and dry it to obtain the M-B-C negative electrode sheet. The loading amount of M-B-C on the electrode is 0.5~1 mg cm −2 , and the conductive agent is super P, acetylene black or Ketjen black, and the binder is PVDF or CMC.
[0016] The single-atom-doped MBC nanosheet material prepared according to the above scheme has a sheet-like or block-like structure of stacked carbon layers as the main body of the material, which is conducive to the rapid transfer of alkali metal ions and ions in the electrolyte; the constituent elements M, B and C of the obtained single-atom-doped MBC nanosheet material are uniformly distributed on the surface of the material, and M exists in the form of highly dispersed single atoms.
[0017] Furthermore, the metal boride can be a commercially available product, or can be prepared by vacuum sealing.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The invention uses metal boride and carbon source as raw materials to synthesize single-atom doped MBC nanomaterials. The raw materials are cheap, the synthesis is simple, the operation is convenient, and the method is suitable for large-scale preparation and application.
[0019] The present invention realizes the controllable preparation of the morphology of single-atom doped MBC nanomaterials by annealing and reduction in an argon-hydrogen atmosphere, exhibits excellent energy storage characteristics, and has important application prospects as negative electrode materials for alkali metal ion batteries (lithium, sodium, potassium). BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a SEM image of the single-atom doped Ti-BC nanosheet prepared in Example 1; Figure 2 is a SEM image of the single-atom doped Mo-BC nanosheet prepared in Example 2; Figure 3 is a SEM image of the single-atom doped Nb-BC nanosheet prepared in Example 3; Figure 4 XRD patterns of single-atom doped MBC materials prepared in Examples 1, 2, 3, 4, 5, and 6; Figure 5 The long cycle performance of lithium, sodium and potassium ion batteries assembled with the single atom doped Ti-BC material obtained in Example 1 as the negative electrode; Figure 6 The long cycle performance of lithium, sodium and potassium ion batteries assembled with the single atom-doped Mo-BC material obtained in Example 2 as the negative electrode. DETAILED DESCRIPTION
[0021] The synthesis of the single-atom doped MBC nanomaterial of the present invention will be further described below with reference to specific examples, but this does not constitute any limitation to the present invention. The graphene in the following examples is few-layer graphene with a layer number of ≤5 and a specific surface area of 188.21 m 2 g -1 The purchasing merchant is Suzhou Tanfeng Graphene Technology Co., Ltd.
[0022] Example 1 A preparation method of a single-atom doped Ti-B-C material includes the following steps: 1) Preparation of the precursor: Add 0.3 g of TiB (purchased from Shanghai Titan Scientific Co., Ltd.) powder into 90 mL of deionized water, stir on a magnetic stirrer for 10 minutes to obtain a suspension, then gradually add 10 mL of hydrogen peroxide (30 wt%) solution dropwise into the suspension, stir for 1 hour until it completely dissolves into a light green liquid, and let it stand for 24 hours to fully react. Add 0.2 g of graphene into the solution, stir on a stirrer for 2 hours until it completely dissolves, and dry it on a freeze dryer (cold well at -50 °C) for two days to obtain a single-atom doped Ti-B-C precursor.
[0023] 2) Annealing treatment: Grind the obtained single-atom doped Ti-B-C precursor with an agate mortar for 20 minutes and then load it into a quartz boat. Under an Ar-H2 (volume ratio of 9:1, hydrogen partial pressure controlled at 0.1 MPa) atmosphere, heat it to 300 °C at a rate of 3 °C / min, hold for 4 hours, and then naturally cool to room temperature to obtain a black powder.
[0024] 3) The preparation process of the atomic doped Ti-B-C material as the negative electrode is as follows. The atomic doped Ti-B-C material, super P, and PVDF are mixed evenly according to a mass ratio of 8:1:1, add an appropriate amount of N-methyl-2-pyrrolidone and grind until there are no obvious particles in the slurry, and evenly coat it on the copper foil with a scraper and dry it to obtain a Ti-B-C negative electrode sheet. The loading amount of Ti-B-C on the electrode is 0.5 - 1 mg cm −2 .
[0025] Figure 1 is the scanning electron microscope image of the product obtained in this example. The results show that: the obtained single-atom doped Ti-B-C presents a nanosheet morphology, and at the same time, there are no obvious metal particles on the material surface, indicating that the metal exists in a highly dispersed form in the material.
[0026] The X-ray diffraction pattern of the single-atom doped Ti-B-C material obtained in this example is shown in Figure 4 . It can be seen that: diffraction peaks appear at the positions of 26° and 44° in the XRD pattern of the obtained sample. By comparing with the standard card of carbon (PDF#75-1621), it can be known that these two peaks are very likely to correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no diffraction peaks of any obvious metal elements are found, further indicating that the metal does not form particles and has a high dispersion degree in the carbon substrate.
[0027] Figure 5The single-atom doped Ti-B-C material obtained in this example was used as the negative electrode to assemble a half-cell. Using K metal as the counter electrode and 3M KFSI / DME solution as the electrolyte, with a voltage range of 0.01 - 3.0V, a constant current charge-discharge test was carried out on LAND CT3001A. It can be seen that: at a current density of 100 mA g −1 after 800 cycles, the discharge specific capacity is 399.2 mAh g −1 , and the Coulombic efficiency after 800 cycles is 99.88%. The Coulombic efficiency is close to 100%, and the long-term cycling is very stable. Further, the single-atom doped Ti-B-C material obtained in the example was used as the negative electrode material, and a half-cell was assembled with lithium metal as the counter electrode. 1.0 M LiPF6 in EC: DMC: DEC = 1: 1: 1 vol% was used as the electrolyte, with a voltage range of 0.01 - 3.0V, and a constant current charge-discharge test was carried out on LAND CT3001A. It can be seen that: at a current density of 100mA g −1 the discharge specific capacity after two cycles is 621 mAh g −1 , and the discharge specific capacity after 800 cycles is 507.6 mAh g −1 , and the Coulombic efficiency after 800 cycles is 99.09%. Using the single-atom doped Ti-B-C material obtained in the example as the negative electrode material, a half-cell was assembled with sodium metal as the counter electrode. 1.0 M NaPF6 in DIGLYME: DME = 1: 1 vol% was used as the electrolyte, with a voltage range of 0.01 - 3.0V, and a constant current charge-discharge test was carried out on LAND CT3001A. It can be seen that: at a current density of 100mA g −1 after 800 cycles, the discharge specific capacity is 320 mAh g −1 , and the Coulombic efficiency after 800 cycles is 99.69%. This verifies the excellent performance of the single-atom doped Ti-B-C material as an alkali metal ion battery.
[0028] Example 2 A preparation method of a single-atom doped Mo-B-C material, comprising the following steps: 1) Preparation of the precursor: Add 0.3 g of MoB (purchased from Shanghai Titan Scientific Co., Ltd.) powder into 90 mL of deionized water, stir on a magnetic stirrer for 10 minutes to obtain a suspension, then gradually add 10 mL of hydrogen peroxide (30 wt%) dropwise into the suspension, stir for 1 hour until it completely dissolves into a light green liquid, and let it stand for 24 hours to fully react. Add 0.2 g of graphene into the solution, stir on a stirrer for 2 hours until it completely dissolves, and dry it in a freeze dryer (cold well -50°C) for two days to obtain a single-atom doped Mo-B-C precursor.
[0029] 2) Annealing treatment: The obtained single-atom doped Mo-B-C precursor was ground in an agate mortar for 20 minutes and then loaded into a quartz boat. It was heated to 300 °C at a rate of 3 °C / min in an Ar-H2 atmosphere (volume ratio 9:1, hydrogen partial pressure controlled at 0.1 MPa), held for 4 hours, and then naturally cooled to room temperature to obtain a black powder.
[0030] 3) The preparation process of the anode using the atom-doped Mo-B-C material is as follows. For the preparation process of the anode using the atom-doped Mo-B-C material, the atom-doped Mo-B-C material, acetylene black, and CMC were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of N-methyl-2-pyrrolidone was added and ground until there were no obvious particles in the slurry. It was evenly coated on a copper foil with a scraper and dried to obtain a Mo-B-C anode sheet. The loading amount of Mo-B-C on the electrode was 0.5 - 1 mg cm −2 .
[0031] Figure 2 This is the scanning electron microscope image of the product obtained in this example. The results show that the obtained single-atom doped Mo-B-C material presents a nanosheet morphology, and there are no obvious metal particles on the material surface, indicating that the metal exists in a highly dispersed form in the material.
[0032] The X-ray diffraction pattern of the single-atom doped Mo-B-C material obtained in this example is shown in Figure 4 , and it can be seen that diffraction peaks appear at 26° and 44° in the XRD pattern of the obtained sample. Comparing with the standard card of carbon (PDF#75-1621), it is very likely that these two peaks correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no diffraction peaks of any obvious metal elements were found, further indicating that the metal did not form particles and had a high degree of dispersion in the carbon substrate.
[0033] Figure 6 This is a half-cell assembled with the single-atom doped Mo-B-C material obtained in this example as the anode, a K metal as the counter electrode, 3M KFSI / DME as the electrolyte, and a voltage range of 0.01 - 3.0 V. A constant current charge-discharge test was carried out on a LAND CT3001A. It can be seen that at a current density of 100 mA g −1 , after 200 cycles, the discharge specific capacity was 360.9 mAh g −1, after 200 cycles, the Coulombic efficiency is 99.85%, and the capacity after cycling hardly decays, showing good stability. Further, the single-atom doped Mo-B-C material obtained in the example can be used as the anode material, and a lithium metal is used as the counter electrode to assemble a half-cell. 1.0 M LiPF6 in EC:DMC:DEC = 1:1:1 vol% is used as the electrolyte, and the voltage range is 0.01~3.0V. Constant current charge-discharge tests are carried out on LAND CT3001A. It can be seen that: the discharge specific capacity after two cycles at a current density of 100 mA g −1 is 711.7 mAh g −1 , the discharge specific capacity after 200 cycles is 635.8 mAh g −1 , the Coulombic efficiency after 200 cycles is 99.39%, and the Coulombic efficiency is close to 100%, indicating very stable cycling. Using the single-atom doped Mo-B-C material obtained in the example as the anode material, a sodium metal is used as the counter electrode to assemble a half-cell. 1.0 M NaPF6 in DIGLYME:DME = 1:1 vol% is used as the electrolyte, and the voltage range is 0.01~3.0V. Constant current charge-discharge tests are carried out on LAND CT3001A. It can be seen that: the discharge specific capacity after two cycles at a current density of 100mA g −1 is 286.5 mAh g −1 , the discharge specific capacity after 200 cycles is 276.3 mAh g −1 , and the Coulombic efficiency after 200 cycles is 99.62%. The excellent performance of the single-atom doped Mo-B-C material as an alkali metal ion battery is verified.
[0034] Example 3 A preparation method of a single-atom doped Nb-B-C material, comprising the following steps: 1) Preparation of the precursor: Add 0.3 g of NbB2 (purchased from Shanghai Titan Scientific Co., Ltd.) powder into 90 mL of deionized water, stir on a magnetic stirrer for 10 minutes to obtain a suspension, and then gradually add 10 mL of hydrogen peroxide (30 wt%) dropwise to the suspension, stir for 1 hour until it is completely dissolved into a light green liquid, and let it stand for 24 hours to fully react. Add 0.2 g of graphene into the solution, stir on a stirrer for 2 hours until it is completely dissolved, and dry it on a freeze dryer (cold well -50 °C) for two days to obtain a single-atom doped Nb-B-C precursor.
[0035] 2) Annealing treatment: The obtained single-atom doped Nb-B-C precursor was ground in an agate mortar for 20 minutes and then loaded into a quartz boat. It was heated to 300 °C at a rate of 3 °C / min in an Ar-H2 (volume ratio 9:1, hydrogen partial pressure controlled at 0.1 MPa) atmosphere, held for 4 hours, and then naturally cooled to room temperature to obtain a black powder.
[0036] Figure 3 Figure 4 is the scanning electron microscope image of the product obtained in this example. The results show that the obtained single-atom doped Nb-B-C material exhibits a nanosheet morphology, and there are no obvious metal particles on the material surface, indicating that the metal exists in a highly dispersed form in the material.
[0037] The X-ray diffraction pattern of the single-atom doped Nb-B-C material obtained in this example is shown in Figure 4 , and it can be seen that diffraction peaks appear at 26° and 44° positions in the XRD pattern of the obtained sample. Comparing with the standard card of carbon (PDF#75-1621), these two peaks are likely to correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no diffraction peaks of any obvious metal elements are found, further indicating that the metal does not form particles and has a high dispersion degree in the carbon substrate.
[0038] Example 4 A preparation method of a single-atom doped Co-B-C material, comprising the following steps: 1) Preparation of the precursor: 0.3 g of CoB (in the preparation process of CoB, Co powder and B powder were mixed evenly in a mass ratio of 1:1, sealed in a quartz tube under a vacuum pressure of 5×10 -5 Pa, and then taken out after holding at 850 °C for 5 hours to obtain CoB raw material.) powder was added to 90 mL of deionized water, stirred on a magnetic stirrer for 10 minutes to obtain a suspension, and then 10 mL of hydrogen peroxide (30 wt%) was added dropwise to the suspension and stirred for 1 hour until it completely dissolved into a light green liquid, and left standing for 24 hours to fully react. 0.2 g of graphene was added to the solution and stirred on a stirrer for 2 hours until it completely dissolved, and then dried in a freeze dryer (cold well -50 °C) for two days to obtain a Co-B-C single-atom doped precursor.
[0039] 2) Annealing treatment: The obtained single-atom doped Co-B-C precursor was ground in an agate mortar for 20 minutes and then loaded into a quartz boat. It was heated to 300 °C at a rate of 3 °C / min in an Ar-H2 (volume ratio 9:1, hydrogen partial pressure controlled at 0.1 MPa) atmosphere, held for 4 hours, and then naturally cooled to room temperature to obtain a black powder.
[0040] The X-ray diffraction pattern of the single-atom doped Co-B-C material obtained in this example is shown in Figure 4, it can be seen that diffraction peaks appear at the positions of 26° and 44° in the XRD pattern of the obtained sample. By referring to the standard carbon card (PDF#75-1621), it can be known that these two peaks are very likely to correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no obvious diffraction peaks of metal elements are found, further indicating that the metal does not form particles and has a high dispersion degree in the carbon substrate.
[0041] Example 5 A preparation method of a single-atom doped V-B-C material, comprising the following steps: 1) Preparation of the precursor: Add 0.3 g of VB (purchased from Shanghai Titan Technology Co., Ltd.) powder into 90 mL of deionized water, stir on a magnetic stirrer for 10 minutes to obtain a suspension, then dropwise add 10 mL of hydrogen peroxide (30 wt%) into the suspension, stir for 1 hour until it completely dissolves into a light green liquid, and let it stand for 24 hours to fully react. Add 0.2 g of graphene into the solution, stir on a stirrer for 2 hours until it completely dissolves, and dry it on a freeze dryer (cold well -50°C) for two days to obtain a single-atom doped V-B-C precursor.
[0042] 2) Annealing treatment: Grind the obtained single-atom doped V-B-C precursor in an agate mortar for 20 minutes, then load it into a quartz boat, and heat it to 300°C at a rate of 3°C / min in an Ar-H2 (volume ratio of 9:1, hydrogen partial pressure controlled at 0.1 MPa) atmosphere, hold for 4 hours, and then naturally cool to room temperature to obtain a black powder.
[0043] The X-ray diffraction pattern of the single-atom doped V-B-C material obtained in this example is shown in Figure 4 , it can be seen that diffraction peaks appear at the positions of 26° and 44° in the XRD pattern of the obtained sample. By referring to the standard carbon card (PDF#75-1621), it can be known that these two peaks are very likely to correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no obvious diffraction peaks of metal elements are found, further indicating that the metal does not form particles and has a high dispersion degree in the carbon substrate.
[0044] Example 6 A preparation method of a single-atom doped W-B-C material, comprising the following steps: 1) Preparation of precursor: Add 0.3 g of WB (purchased from Shanghai Titan Scientific Co., Ltd.) powder into 90 mL of deionized water, stir on a magnetic stirrer for 10 minutes to obtain a suspension, then gradually add 10 mL of hydrogen peroxide (30 wt%) dropwise into the suspension, stir for 1 hour until it completely dissolves into a light green liquid, and let it stand for 24 hours to fully react. Add 0.2 g of graphene into the solution, stir on a stirrer for 2 hours until it completely dissolves, and dry it on a freeze dryer (cold well at -50 °C) for two days to obtain a W-B-C single-atom doped precursor.
[0045] 2) Annealing treatment: Grind the obtained single-atom doped W-B-C precursor in an agate mortar for 20 minutes, then load it into a quartz boat, heat it to 300 °C at a rate of 3 °C / min in an Ar-H2 (volume ratio of 9:1, hydrogen partial pressure controlled at 0.1 MPa) atmosphere, hold for 4 hours, and then naturally cool to room temperature to obtain a black powder.
[0046] The X-ray diffraction pattern of the single-atom doped W-B-C material obtained in this example is shown in Figure 4 , and it can be seen that diffraction peaks appear at the positions of 26° and 44° in the XRD pattern of the obtained sample. By comparing with the standard card of carbon (PDF#75-1621), it can be known that these two peaks are very likely to correspond to the (002) and (101) crystal planes of graphite carbon. In addition, no obvious diffraction peaks of metal elements are found, further indicating that the metal does not form particles and has a high dispersion degree in the carbon substrate.
[0047] The above is only the preferred embodiment of the present invention. It should be pointed out that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A preparation method of single-atom doped M-B-C material, characterized in that, It includes the following steps: 1) Disperse metal boride in water, add hydrogen peroxide and stir until the metal boride dissolves. After standing for at least 20 h, add graphene and stir at room temperature until a homogeneous solution is obtained, and then freeze-dry; 2) Anneal the dried product obtained in step 1) in an argon / hydrogen mixed atmosphere, and cool to room temperature to obtain the product.
2. The preparation method according to claim 1, wherein The metal boride described in step 1) is titanium boride, molybdenum boride, niobium diboride, cobalt boride, vanadium boride, tungsten boride, iron boride, zirconium diboride, chromium diboride, magnesium diboride or aluminum diboride; the ratio of the metal boride to hydrogen peroxide is (0.2~0.5) g:(10~30) mL.
3. The preparation method according to claim 1, characterized in that In step 1), the mass ratio of the graphene to the metal boride is (1~3):1, and the number of layers of the graphene ≤ 5 layers.
4. The preparation method according to claim 1, characterized in that, In step 1), the temperature of the freeze-drying is -30~-50 °C, and the time of the freeze-drying is 24 h~72 h.
5. The preparation method according to claim 1, wherein, In the argon / hydrogen mixed atmosphere described in step 2), the volume ratio of argon to hydrogen is (8~10):1, and the hydrogen partial pressure is controlled at 0.1~0.3 MPa.
6. The preparation method according to claim 1, wherein The annealing temperature described in step 2) is 300~350 °C; the heating rate used is 2~5 °C / min, and the holding time is 3~5 h.
7. A single-atom doped M-B-C material prepared by the preparation method according to any one of claims 1 to 6.
8. Application of the single-atom doped M-B-C material according to claim 7 in lithium, sodium or potassium ion batteries.
9. The application according to claim 8, characterized in that, The single-atom doped M-B-C material is used as an active substance and coated on a current collector as a negative electrode.
10. The application according to claim 9, wherein Mix the atom-doped M-B-C material, conductive agent, and binder uniformly in a ratio of (6~8):(1~3):1, add an appropriate amount of NMP or water, and grind until there are no obvious particles in the slurry. Then coat it evenly on the copper foil and dry to obtain the M-B-C negative electrode sheet. The loading amount of M-B-C on the electrode is 0.5~1 mg cm −2 , where the conductive agent is super P, acetylene black, or Ketjen black, and the binder is PVDF or CMC.